Mixed Germ Cell Tumor with Extensive Yolk Sac Tumor Elements in the Frontal Lobe of an Adult - Toshihide Takahashi; Eiichi Ishikawa; Yosuke Masuda; Tetsuya Yamamoto; Taiki Sato; Makoto Shibuya; Akira Matsumura (Case Reports in Surgery)
Intracranial nongerminomatous germ cell tumors (NGGCTs) in unusual locations are extremely rare. Here, we report a case of a yolk sac tumor in the frontal lobe in a middle-aged patient. A 42-year-old man was admitted to our hospital for headache and nausea. Magnetic resonance imaging (MRI) showed an enhanced mass lesion with a marked cyst component. The serum alpha-fetoprotein (αFP) level was extremely high. Histological examination of specimens after subtotal removal revealed a primary mixed germ cell tumor with extensive yolk sac tumor elements, often referred to as an intracranial “yolk sac tumor.” The preoperative diagnosis of NGGCTs in unusual age and locations is extremely difficult. Clinicians should consider the possibility of NGGCTs, including yolk sac tumors, when intracranial tumors with unusual MRI findings are encountered.